Libertarian Paternalism and Self-Government Housing Policy in Poland - Brzezicka, Justyna; Wiśniewski, Radosław; Napiórkowska-Baryła, Agnieszka (Olsztyn Economic Journal, 2016)
The article pertains to the issue of libertarian paternalism in relation to public housing policy in Poland. Libertarian paternalism is an idea developing on behavioral grounds, the main task of which is ensuring paternalistic protection and social care by the government and local self-government administrative organs, while at the same time maintaining the society's freedom of choice and increasing social-economic well-being. In the article, the issue of libertarian paternalism is described, a set of instruments of the described concept is implemented for purposes of working out solutions to problems connected with the housing policy of territorial self-government units in Poland (communes), and the proposed solutions validated in a post-socialist country. The work is of a conceptual-remedial character. Within it, selected tools in the scope of behaviorally informed interventions, serving to implement solutions that increase the effectiveness, efficiency and economy of operations of public organizations under conditions of dynamic decentralizing changes, have been indicated. The most important conclusions arising from the deliberations carried out make it possible to look at housing policy in Poland through a prism of a modern market economy.